On Composite l(m, n)-Kummer’s Matrix Functions of two Complex Variables: Ayman Shehata Mohammed, Rashwan Ahmed Rashwan, Mohamed S Metwally, Mahmoud Tawfik Mohamed - Team, Support (Thai Journal of Mathematics, 2016)
The main aim of this paper is to define and study of a new kummer’s matrix function, say, compositel (m; n)-Kummer’s matrix function of two complex variables. The radius of regularity and recurrencerelation on this function is established. The effect of differential operator (D) on this function isinvestigated and a solution of certain partial differential equation is established.